2017
DOI: 10.1080/07399332.2017.1296842
|View full text |Cite
|
Sign up to set email alerts
|

Recent im/migration to Canada linked to unmet health needs among sex workers in Vancouver, Canada: Findings of a longitudinal study

Abstract: Despite universal health care in Canada, sex workers (SW) and im/migrants experience suboptimal health care access. In this analysis, we examined the correlates of unmet health needs among SWs in Metro Vancouver over time. Data from a longitudinal cohort of women SWs (AESHA) was used. Of 742 SWs, 25.5% reported unmet health needs at least once over the 4-year study period. In multivariable logistic regression using generalized estimating equations, recent im/migration had the strongest impact on unmet health n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…International migrants frequently described concerns regarding their legal status as among the most important reasons they did not receive the SRH care they needed. These findings complement previous research conducted with migrant sex workers, which has found that they frequently face enhanced barriers to healthcare access compared with native‐born populations, for reasons that include a lack of financial resources, experiences of stigma, and their legal status, which jointly contribute to limited access to and seeking of care.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…International migrants frequently described concerns regarding their legal status as among the most important reasons they did not receive the SRH care they needed. These findings complement previous research conducted with migrant sex workers, which has found that they frequently face enhanced barriers to healthcare access compared with native‐born populations, for reasons that include a lack of financial resources, experiences of stigma, and their legal status, which jointly contribute to limited access to and seeking of care.…”
Section: Discussionsupporting
confidence: 86%
“…Previous research has documented poor access to SRH services and rights (for example, limited access to contraceptives or safe abortion) among sex workers across diverse settings including the Mexico–USA border, Canada, and Sub‐Saharan Africa . However, there remains a critical research gap in understanding migrant sex workers' access and unmet need for SRH services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual-level characteristics included age, HIV seropositivity (assessed through voluntary bioLytical INSTI rapid tests for HIV screening), identifying as a gender and/or sexual minority (defined as 'yes' to any of gay, lesbian, bisexual, queer, two spirit, asexual, transgender, intersex, transsexual, genderqueer, other), ethnicity (categorized as white, indigenous, or other minority), and injection and noninjection illicit drug use (e.g., crack cocaine, crystal meth, heroin, diversion of prescription opiates). Structural factors included whether or not the participant was an im/migrant to Canada, time since migration to Canada (5 years vs. >5 years) (Sou et al, 2017), and country of birth (categorized as Canada, non-HBV-endemic country, or HBV-endemic country). Healthcare access factors studied included ever having used sexual and reproductive health (SRH) services in Vancouver, and engagement in HCV, STI, and HIV testing.…”
Section: Variablesmentioning
confidence: 99%
“…SHS has a prevalence of higher than 65% in China [10][11][12][13]. and become an increasingly concerned problem in many other countries [14,15]. Moreover, the prevalence may be severely underestimated since many individuals may not know that they suffer from SHS.…”
Section: Introductionmentioning
confidence: 99%